Non-coding RNAs: the extensive and interactive regulators of the blood-brain barrier permeability. (15th October 2021) - Yang, Ruicheng; Xu, Bojie; Yang, Bo; Fu, Jiyang; Chen, Huanchun; Wang, Xiangru
ABSTRACT: The blood-brain barrier (BBB), which controls permeability into and out of the nervous system, is a tightly connected, structural, and functional separation between the central nervous system (CNS) and circulating blood. CNS diseases, such as Alzheimer's disease, multiple sclerosis, traumatic brain injury, stroke, meningitis, and brain cancers, often develop with the increased BBB permeability and further leads to irreversible CNS injury. Non-coding RNAs (ncRNAs) are functional RNA molecules that generally lack the coding abilities but can actively regulate the mRNA expression and function through different mechanisms. Various types of ncRNAs, including microRNAs (miRNAs), long ncRNAs (lncRNAs), and circular RNAs (circRNAs), are highly expressed in brain microvascular endothelial cells and are potential mediators of BBB permeability. Here, we summarized the recent research progress on miRNA, lncRNA, and circRNA roles regulating the BBB permeability in different CNS diseases. Understanding how these ncRNAs affect the BBB permeability shall provide important therapeutic insights into the prevention and control of the BBB dysfunction.